2012
DOI: 10.1051/0004-6361/201118026
|View full text |Cite
|
Sign up to set email alerts
|

SST/CRISP observations of convective flows in a sunspot penumbra

Abstract: Context. Recent discoveries of intensity correlated downflows in the interior of a sunspot penumbra provide direct evidence for overturning convection, adding to earlier strong indications of convection from filament dynamics observed far from solar disk center, and supporting recent simulations of sunspots. Aims. Using spectropolarimetric observations obtained at a spatial resolution approaching 0. 1 with the Swedish 1-m Solar Telescope (SST) and its spectropolarimeter CRISP, we investigate whether the convec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 66 publications
4
26
0
1
Order By: Relevance
“…As a consequence, magnetic field with inverse polarity and downflow velocities should be observed all along the boundaries of bright penumbral filaments. While observational evidence for convective downflows in the whole penumbra has been recently reported (Scharmer et al 2011;Scharmer & Henriques 2012;Joshi et al 2011), the reversed flux has only been observed in the outer penumbra (Westendorp Plaza et al 1997del Toro Iniesta et al 2001). But even with the highest spatial resolution spectropolarimetry, we have been unable to observe them in the inner penumbra (Langhans et al 2005).…”
Section: Introductionmentioning
confidence: 53%
“…As a consequence, magnetic field with inverse polarity and downflow velocities should be observed all along the boundaries of bright penumbral filaments. While observational evidence for convective downflows in the whole penumbra has been recently reported (Scharmer et al 2011;Scharmer & Henriques 2012;Joshi et al 2011), the reversed flux has only been observed in the outer penumbra (Westendorp Plaza et al 1997del Toro Iniesta et al 2001). But even with the highest spatial resolution spectropolarimetry, we have been unable to observe them in the inner penumbra (Langhans et al 2005).…”
Section: Introductionmentioning
confidence: 53%
“…Contrary to the claims of Franz & Schlichenmaier (2009 and Puschmann et al (2010a), the presence of downflows in the inner penumbra has been reported by Sánchez Almeida et al (2007), Joshi et al (2011), Scharmer et al (2011) and Scharmer & Henriques (2012 1 . In a recent study, Scharmer et al (2013) report narrow downflow lanes to be located at the boundaries between spines and inter-spines.…”
Section: Structure Of Penumbral Filamentsmentioning
confidence: 64%
“…Indirect support for azimuthal convection was put forward by Ichimoto et al (2007a), Zakharov et al (2008), Spruit et al (2010), Bharti et al (2010), although an alternative explanation of some of these observations in terms of waves has also been provided (Bharti et al 2012). Recent observations from the Swedish Solar Telescope (SST: Scharmer et al 2003)/CRisp Imaging Spectro-Polarimeter (CRISP) showed downflows in the inner penumbra and a qualitative association of upflows with hot and downflows with cool gas in the deep photosphere (Joshi et al 2011;Scharmer et al 2011;Scharmer & Henriques 2012). A&A 557, A25 (2013) However, some other researchers did not detect such flow patterns (Franz & Schlichenmaier 2009;Bellot Rubio et al 2010;Puschmann et al 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…This value is larger than the theoretical diffraction-limited FHWM of ≈ 0.27" 1 . While we have not investigated in detail the reason for this worse-than-ideal performace we can point to a number of possible sources such as high-altitude seeing (Scharmer & Henriques 2012;Löfdahl & Scharmer 2012), width of the spectrograph's slit, and slightly off-focus spectrograph.…”
Section: Estimation Of P N and σ Nmentioning
confidence: 94%